2014
DOI: 10.1093/jpepsy/jsu046
|View full text |Cite
|
Sign up to set email alerts
|

Audio-Video Recording of Health Care Encounters for Pediatric Chronic Conditions: Observational Reactivity and Its Correlates

Abstract: Most recordings included slight evidence of participant camcorder awareness. But there was negligible evidence that camcorder awareness influenced clinic visit communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
(22 reference statements)
3
20
0
Order By: Relevance
“…Food parenting practices play an important role in shaping child food preferences and eating patterns (Birch, 1999). Responsive practices that attend to child’s cues of hunger and fullness, make healthy foods available and accessible and facilitate children’s autonomy in food selection and energy regulation, are found to be protective against childhood obesity (Pinquart, 2014; Sleddens et al, 2014). On the other hand, unresponsive food parenting practices are characterized by a lack of reciprocity between parent and child and serve to limit children’s food autonomy and disregard their satiety cues (Birch & Ventura, 2009; Black & Aboud, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Food parenting practices play an important role in shaping child food preferences and eating patterns (Birch, 1999). Responsive practices that attend to child’s cues of hunger and fullness, make healthy foods available and accessible and facilitate children’s autonomy in food selection and energy regulation, are found to be protective against childhood obesity (Pinquart, 2014; Sleddens et al, 2014). On the other hand, unresponsive food parenting practices are characterized by a lack of reciprocity between parent and child and serve to limit children’s food autonomy and disregard their satiety cues (Birch & Ventura, 2009; Black & Aboud, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction was measured on a 5-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). The study that used the larger sample from which we drew our obesity subsample reported alpha coefficients of 0.92 for youths and 0.94 for parents for the total scale (Antal et al, 2015). Test-retest reliability from Visit 1 to Visit 2 was r = 0.73 for youth and r = 0.53 for parents; from Visit 2 to Visit 3 it was r = 0.74 for youth and r = 0.63 for parents (p < 0.01 for all).…”
Section: Treatment Alliance Scale (Tas)mentioning
confidence: 99%
“…The larger study conducted that included multiple subspecialty groups, including obesity, reported coefficient alpha of 0.96 for the PGMP (Antal et al, 2015). The 11-item "care provider" section was completed by parents at Visit 1, 2, and 3, permitting analyses of how treatment satisfaction is associated with contextual variables, aspects of the communication process, proximal outcomes and study endpoints.…”
Section: Press-ganey Medical Practice Survey (Pgmp)mentioning
confidence: 99%
“…Other researchers have been more specific about the participant reactivity encountered in their research with children. For example, Antal et al (2015) reported that children oriented to the video camera at least once in 74% of their recordings of visits with pediatric health care providers. Children displayed more orientations to the camera than did their parents or health care providers, with 5-to 7-year-old children displaying orientations six times more often than children over age 13 (Antal et al, 2015).…”
mentioning
confidence: 99%
“…For example, Antal et al (2015) reported that children oriented to the video camera at least once in 74% of their recordings of visits with pediatric health care providers. Children displayed more orientations to the camera than did their parents or health care providers, with 5-to 7-year-old children displaying orientations six times more often than children over age 13 (Antal et al, 2015). Overall, these orientations made up a very small proportion of the total behaviours coded by the researchers (Antal et al, 2015).…”
mentioning
confidence: 99%